2005
DOI: 10.1002/bip.20423
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the conformational profile of trishomocubane amino acid dipeptide

Abstract: 4-Amino-(D3)-trishomocubane-4-carboxylic acid is a constrained alpha-amino acid residue that exhibits promising conformational characteristics, i.e., helical and beta-turns. As part of the development of conformational guidelines for the design of peptides and protein surrogates, the conformational energy calculations on trishomocubane using molecular mechanics and ab initio methods are presented. The C(alpha) carbon of trishomocubane forms part of the cyclic structure, and consequently a peptidic environment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Polycyclic cage hydrocarbons act as valuable synthons in pharmaceutical and medicinal chemistry (Bisetty et al, 2006;Geldenhuys, et al, 2005). They are also useful candidates in energetic materials (Zhang et al, 2018).…”
Section: Structure Descriptionmentioning
confidence: 99%
“…Polycyclic cage hydrocarbons act as valuable synthons in pharmaceutical and medicinal chemistry (Bisetty et al, 2006;Geldenhuys, et al, 2005). They are also useful candidates in energetic materials (Zhang et al, 2018).…”
Section: Structure Descriptionmentioning
confidence: 99%
“…Table 1 lists the 29 α-tetrasubstituted α-amino acids whose intrinsic conformational propensities have been determined to date using ab initio or DFT quantum mechanical methods2037 according to a literature search. This list is expected to be dynamic and thus be updated when studies on new compounds in this category are reported.…”
Section: α-Tetrasubstituted α-Amino Acidsmentioning
confidence: 99%
“…Our force field calculations using AMBER 5.0 along with ab initio calculations indicated that both cage amino acids (1 and 2) are characterized by four low-energy conformers corresponding to the C 7ax , C 7eq , 3 10 and a L helical structures (35)(36)(37)(38)(39)(40). We have previously predicted the following after a theoretical study of the peptide segment Ala-Cage-Ala: 'This means that the system of three peptide units may be taken as a ''block'', and such blocks may then serve as excellent places for folding back in a polypeptide chain, enabling the formation of a cyclic chain structure' (39).…”
mentioning
confidence: 95%
“…In this study, we have built on our previous computational studies (35)(36)(37)(38)(39)(40). It was predicted that the two pentacycloundecane amino acids (1 and 2; 41-43) should introduce strong b-turn characteristics to peptides.…”
mentioning
confidence: 99%